Pengaruh Kualitas Pelayanan terhadap Loyalitas melalui Kepuasan Pelanggan sebagai Variabel Intervening (Studi Kasus Pada Penumpang Shuttle PO. Sumber Alam Jurusan Semarang-Cilacap) - Setyaningriani, Eka Dewi; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2017)
PO. Sumber Alam is one of the transportation service providers offering shuttle service. Like other PO Otobus Companies. PO. Sumber Alam is always trying to meet and satisfy the desires of its customers in the hope that customers can feel satisfied and loyal to continue to use the services of PO. Sumber Alam, but in fact according to the management of the number of passengers PO. Sumber Alam in the last 3 years continued to decline significantly, especially from 2015 to 2016, which amounted to 57,480 passengers. By looking at the existing problems, the purpose of this study is to analyze the effect of service quality on customer satisfaction and its impact on customer loyalty PO Sumber Alam. Sampling technique used is nonprobability sampling that is purposive sampling. The sample of this study amounted to 100 customers of PO Sumber Alam Semarang-Cilacap department and the opposite direction. Respondents' answers will be processed using various tests of validity test, reliability test, classical assumption test, simple linear regression analysis, correlation coefficient, determination coefficient and t test using SPSS program Statistical version for Social Science for Windows 16.00. Based on the analysis, it can be concluded that service quality positively affects customer loyalty, service quality positively affects customer satisfaction, and customer satisfaction positively influences customer loyalty. The suggestion of this research is PO. Sumber Alam needs to make improvements or rejuvenation of the physical appearance of the fleet, adding to the completeness of the facilities at the shuttle location and providing guidance and training for employees, so that employees can provide better service to customers.